Exploring the challenges of virtual internships during the COVID-19 pandemic and their potential influence on the professional identity of health professions students: A view from Qatar University - Bawadi, Hiba; Shami, Rula; El-Awaisi, Alla; Al-Moslih, Ayad; Abdul Rahim, Hanan; Du, Xiangyun; Moawad, Joyce; Al-Jayyousi, Ghadir Fakhri (Frontiers in Medicine, 2023)
Introduction COVID-19 has imposed many shared limitations on medical and health education. Just like other health professions programs at most institutions, the Qatar University health cluster (QU Health) applied a containment approach and shifted all learning online, and onsite training was replaced by virtual internships (VIs) during the first wave of the pandemic. Our study aims to explore the challenges of virtual internships during the COVID-19 pandemic and their influence on the professional identity (PI) of the health cluster students from the College of Medicine, the College of Health Sciences, and the College of Pharmacy at Qatar University. Methods A qualitative approach was employed. In total, eight focus groups with students (N = 43) and 14 semi-structured interviews with clinical instructors from all the health cluster colleges were conducted. Transcripts were analyzed following the inductive approach. Results The major challenges reported by students were mainly related to the lack of the required skills for navigating the VI, professional and social stressors, the nature of VIs and the quality of learning, technical and environmental issues, and the development of students' professional identity in an alternative internship environment. The challenges relating to the development of professional identity included: limited clinical (practical) experience, a lack of experience in fighting a pandemic, a lack of communication and feedback, and a lack of confidence in meeting the internship's goals. A model was constructed to represent these findings. Discussion The findings are important in identifying the inevitable barriers to virtual learning for health professions students and provide a better understanding of how such challenges and different experiences would be affecting the development of their PI. Hence, students, instructors, and policymakers alike should strive to minimize these barriers. Since physical interactions and patient contact are indispensable components of clinical teaching, these extraordinary times demand innovations involving technology and simulation-based teaching. There is a need for more studies that are focused on determining and measuring the short- and long-term effects of the VI on students' PI development.